Optimasi Efisiensi Solar Cell Melalui Solar Tracking dan Sistem Monitoring Pada Proteksi Energi Listrik - Ahmad Baihaqi, Mas; Abdillah, Hartawan; Izzuddin, Ahmad; Asrori, Tamam; Muhammad, Alief; Hari Tunggal Prasettio, Dani (Journal Electric Field, 2024)
This research aims to design and develop an advanced monitoring system for solar cells, incorporating solar tracking technology and equipped with an energy storage protection system. In Indonesia, the substantial potential of solar energy remains underutilized, despite the country's advantageous equatorial location, which provides a solar radiation intensity averaging 4.5 kWh/m² per day. The proposed system in this study seeks to maximize solar energy capture by employing a tracking mechanism that aligns the solar cells with the direction of sunlight throughout the day. Additionally, the system is designed with an integrated protection feature to prevent battery overuse, thereby extending the battery's lifespan and ensuring efficient energy storage. The research utilizes an Arduino Uno microcontroller, Light Dependent Resistor (LDR) sensors, and an INA219 sensor module as the primary components for accurate measurement and real-time monitoring. The system's effectiveness is evaluated based on its ability to optimize solar energy reception and maintain the longevity and efficiency of the energy storage system. Experimental results demonstrate that the developed system significantly improves the efficiency of solar energy capture by the solar cells and provides robust protection for the energy storage mechanism. This study contributes to the field of renewable energy by offering a practical solution for enhancing solar energy utilization in regions with high solar irradiance, thus promoting sustainable energy practices and reducing dependence on non-renewable energy sources.